Copper-based alloy friction plate of torque limiter of wind power coupler

A copper-based alloy friction material for wind turbine torque limiters addresses the issue of high maintenance costs and low precision by enhancing fatigue life and torque control precision, using a specific composition and manufacturing process.

CN120311070APending Publication Date: 2025-07-15HUNAN YILIN MATERIAL TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411427502.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-07-15

AI Technical Summary

Technical Problem

The existing domestic wind power coupling torque limiter friction plate has short fatigue life, high maintenance cost, poor safety and reliability, and is expensive to rely on foreign imports.

Method used

Powder metallurgical high-performance copper-based alloy friction sheets with mass ratios of 9-14%, tin 1-3%, friction components 2-8%, iron 12-18%, nickel 0-3%, and copper as the balance are prepared through specific process steps, including mixing, forming, sintering and mechanical processing, controlling the ratio of particulate carbon to chopped carbon fibers, and optimizing material performance.

Benefits of technology

It significantly improves the fatigue life of the friction plate by more than 60%, significantly improves the torque control accuracy, moderate material density, excellent mechanical performance, and meets the requirements of use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120311070A_ABST
    Figure CN120311070A_ABST
Patent Text Reader

Abstract

The invention relates to a powder metallurgy high-performance copper-based alloy friction plate for a torque limiter of a wind power coupler and a preparation method of the friction plate. The friction plate is composed of, by mass, 9%-14% of carbon, 1%-3% of tin, 2%-8% of friction components, 12%-18% of iron, 0%-3% of nickel and the balance copper. The preparation method comprises the steps of burdening, mixing, forming, sintering and machining. The prepared high-performance copper-based alloy friction plate is particularly suitable for a torque limiter of a wind power generation coupler. The alloy disclosed by the invention is reasonable in component design, simple and controllable in preparation process, easy to realize batch, large-scale and automatic production, high in production efficiency, energy-saving and moderate in cost; the obtained product is excellent in performance, and can greatly improve the torque control precision, save the maintenance cost and improve the operation safety and reliability of wind power equipment when being applied to a wind power coupling torque limiter.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a powder metallurgy high-performance copper-based alloy friction plate for a wind power coupling torque limiter, belonging to the technical fields of powder metallurgy technology, new materials, and the manufacturing technology of wind power equipment components. Background Art

[0002] The friction plate of a wind power coupling torque limiter is a core component in wind power equipment, and its main function is to transmit wind power kinetic energy and protect the safe operation of wind power equipment. Before operation, a certain static pressure is applied to the friction plate. When the external wind power kinetic energy changes and exceeds the design value, under the action of external force, the friction plate and its mating part move relative to each other to release the overload force, so that the entire power generation transmission system will not fail due to overload. During normal operation, the torque limiter plays the role of transmitting wind power kinetic energy. The characteristics of the torque limiter friction plate are that it has a suitable static friction coefficient and a dynamic friction coefficient close to it, meeting the functional design requirements, and at the same time should have the characteristics of reducing friction and wear, and maximizing the service life of the torque limiter.

[0003] For a long time, the friction plates used in wind power coupling torque limiters mainly relied on foreign imports, which were expensive. The fatigue life and slip stroke of domestic friction plates were less than 60,000 degrees under application conditions, seriously affecting the service life of wind power equipment, with high maintenance costs, low torque control accuracy, and poor safety and reliability. A powder metallurgy high-performance copper-based alloy friction plate for a wind power coupling torque limiter of the present invention is of great significance for promoting the development of the country's green energy. Summary of the Invention

[0004] The first technical problem to be solved by the present invention is to design a powder metallurgy high-performance copper-based alloy material formula that meets the requirements of the friction plate of a wind power coupling torque limiter. That is, the friction plate manufactured with this formula has excellent friction and wear characteristics, a suitable static friction coefficient and a dynamic friction coefficient close to it, and at the same time has shear strength and compressive strength that meet the use requirements.

[0005] The second technical problem to be solved by the present invention is to provide a preparation method for a powder metallurgy high-performance copper-based alloy friction plate of a wind power coupling torque limiter.

[0006] A copper-based alloy friction plate for a wind power coupling torque limiter of the present invention is composed of the following components in mass ratio:

[0007] Carbon 9-14%, tin 1-3%, friction component 2-8%, iron 12-18%, nickel 0-3%, and the balance is copper;

[0008] The copper-based alloy friction plate of the wind power coupling torque limiter is prepared by the following steps:

[0009] Step 1: Batching

[0010] Weigh the copper, carbon, tin, friction component, iron, and nickel component materials according to the designed alloy composition ratio. At the same time, add micro-powder paraffin powder at 0.4 - 0.6% of the total mass of the materials; add aviation kerosene at 0.3 - 0.5% of the total mass of the materials. The micro-powder paraffin powder and aviation kerosene are removed during the sintering process. The copper, tin, iron, and nickel are added in the form of master alloy powder, the carbon is added in the form of granular carbon and short carbon fiber, and the friction component is added in the form of compound powder; the mass ratio of granular carbon to short carbon fiber is 9 - 15:0.5 - 2, preferably, in terms of mass ratio, the granular carbon: short carbon fiber is greater than or equal to 5 and less than or equal to 12.

[0011] Step 2: Mixing and forming

[0012] Mix the weighed material powders evenly and place them in a steel mold, and press them with a forming pressure of 450 - 550 MPa to obtain a powder compact. When applied industrially, the pressure can be maintained for 1 - 2 seconds, and the effect is better.

[0013] Step 3: Sintering

[0014] In an atmosphere of cracked ammonia, heat the powder compact to 500 - 550 °C and hold for 0.5 - 1 hour. After the holding is completed, continue to heat to 950 - 990 °C and hold for 2 - 2.5 hours, then cool to below 100 °C and take out of the furnace to obtain a sintered blank of the copper-based alloy friction plate.

[0015] Step 4: Machining

[0016] According to the designed dimensional requirements, machine the obtained sintered blank of the copper-based alloy friction plate to obtain the finished friction plate.

[0017] Preferably, a copper-based alloy friction plate for a wind power coupling torque limiter of the present invention is composed of the following components in terms of mass ratio:

[0018] Carbon 11.5 - 13%, tin 2 - 3%, friction component 2 - 4%, iron 16 - 18%, nickel 0 - 2%, and the balance is copper.

[0019] When applied industrially, the friction component is selected from at least one of aluminum oxide, zirconia, silicon carbide, and silicon oxide.

[0020] Preferably, a copper-based alloy friction plate for a wind power coupling torque limiter of the present invention is composed of the following components in terms of mass ratio:

[0021] Carbon 12 - 12.8%, tin 2 - 3%, friction component 2 - 2.2% or 3.8 - 4%, iron 16.8 - 18%, and the balance is copper.

[0022] In a copper-based alloy friction plate for a torque limiter of a wind power coupling of the present invention, in step one, the metal powder is sieved through a 320-mesh sieve, and the undersize material is taken; the metal powder provides copper, tin, iron, and nickel in the copper-based alloy friction plate for the torque limiter of the wind power coupling. The average particle size of the granular carbon is less than or equal to 200 um, the length of the chopped carbon fiber is 0.4 - 2 mm, preferably 0.5 - 1.5 mm, and the diameter is 5 - 10 microns; the average particle size of the friction component powder is 150 um.

[0023] In the present invention, carbon is provided by two carbon sources with different particle sizes and morphologies. By controlling the ratio of the two, the purpose of enhancing the matrix material and improving the friction and wear properties of the material can be achieved. In order to further improve the shear strength and compressive strength of the product and appropriately reduce the friction coefficient, the mass ratio of the granular carbon to the chopped carbon fiber is controlled to be 11:1.2 - 1.8.

[0024] In a copper-based alloy friction plate for a torque limiter of a wind power coupling of the present invention, the mixing is completed in a three-dimensional drum mixer, and the mixing time is 1.5 - 2.5 hours.

[0025] In a copper-based alloy friction plate for a torque limiter of a wind power coupling of the present invention, in step two, the density of the powder compact is 5.8 - 5.9 g / cm 3 。

[0026] In a copper-based alloy friction plate for a torque limiter of a wind power coupling of the present invention, in step three, the heating rate is 6 - 8 °C / min; the cooling rate is 4 - 6 °C / min.

[0027] In a copper-based alloy friction plate for a torque limiter of a wind power coupling of the present invention, after holding at 500 - 550 °C until the end in step three, a pressure of 2 - 3 MPa is applied to the powder compact material and the pressure is maintained until sintering and cooling are completed.

[0028] In a copper-based alloy friction plate for a torque limiter of a wind power coupling of the present invention, in step three, the density of the sintered compact of the copper-based alloy friction plate is 5.9 - 6.1 g / cm 3 。

[0029] In a copper-based alloy friction plate for a torque limiter of a wind power coupling of the present invention, the shear strength of the sintered compact of the copper-based alloy friction plate obtained in step three is 30 - 35 MPa, the compressive strength is 300 - 330 MPa, preferably 310 - 330 MPa, further preferably 315 - 330 MPa, and the hardness is HBW40 - 48.

[0030] In a copper-based alloy friction plate for a torque limiter of a wind power coupling of the present invention, the obtained copper-based alloy friction plate for the torque limiter of the wind power coupling is applied under a specific pressure of 35 MPa, the service life is that the slipping stroke exceeds 100,000 degrees (preferably 104,000 - 135,000 degrees), and the change rate of the torque calibration value does not exceed ±10%.

[0031] In the powder metallurgy high-performance copper-based alloy friction plate material of the wind power coupling torque limiter of the present invention, the solid lubricant particles have a relatively high carbon content, and the particulate carbon and carbon fiber are uniformly distributed in the matrix material. After optimizing the ratio between the two, not only the anti-friction and wear-resistant properties of the finished product are improved, helping to stabilize the static friction coefficient of the material and the similar dynamic friction coefficient, thereby effectively ensuring the fatigue life of the friction plate and improving the torque control accuracy of the torque limiter, but also it is beneficial to improve the shear strength and compressive strength of the product. At the same time, the density of the friction plate material of the wind power coupling torque limiter of the present invention is controlled between 5.9 - 6.1 g / cm 3 ³, with moderate mechanical properties, fully meeting the requirements for the mechanical properties of the material in use. Appropriate amounts of iron, tin, nickel, and friction component components are added to the material, and the synergistic effect of each component significantly improves the mechanical properties of the material and optimizes the friction and wear properties of the material. Due to the above-mentioned component ratio and preparation method adopted in the present invention, the friction plate of the wind power coupling torque limiter prepared contains component elements with appropriate proportions and a uniformly distributed microstructure of each phase. Compared with other friction plate materials of wind power coupling torque limiters, it has better friction and wear properties, and appropriate and similar static friction coefficients and dynamic friction coefficients. Under the same conditions, the fatigue life is increased by more than 60%, and the torque control accuracy of the torque limiter is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a physical diagram of the torque limiter obtained in Example 2;

[0033] Figure 2 It is a physical diagram of the product obtained in Comparative Example 1 after a crushing test;

[0034] Figure 3 It is a physical diagram of the product obtained in Example 1 after a fatigue test;

[0035] Figure 4 It is a physical diagram of the pre-grinding test of the product obtained in Example 1;

[0036] Figure 5 It is a friction test curve of the product obtained in Example 1;

[0037] Figure 6 It is a friction test curve of the product obtained in Example 2;

[0038] Figure 7 It is an electron microscope photograph of the product obtained in Example 1;

[0039] Figure 8 It is an electron microscope photograph of the product obtained in Example 2. DETAILED DESCRIPTION OF THE INVENTION

[0040] In the embodiments and comparative examples, the metal powder used is passed through a 320-mesh sieve and the material under the sieve is taken; the metal powder used provides copper, tin, iron and nickel in the copper-based alloy friction plate of the wind power coupling torque limiter, the average particle size of the granular carbon is less than or equal to 200um, the length of the short-cut carbon fiber has been clearly recorded in the specific embodiments and comparative examples, and its diameter is 5-10 microns; the average particle size of the friction component powder is 150um.

[0041] Comparative Example 1

[0042] A powder metallurgy high-performance copper alloy friction plate for a wind power coupling torque limiter is prepared, wherein the copper is 73wt%, the iron is 13wt%, the flake graphite is 9wt%, the tin is 3wt%, the nickel is 0wt%, and the aluminum oxide is 2wt%. In addition, 0.4wt% of micro powder paraffin is added according to the total amount, and 0.3wt% of aviation kerosene is added. The preparation process comprises the following steps: putting the weighed materials into a three-dimensional drum mixer for mixing for 1.5 hours; pressing the powder blank in a steel mold with a pressing force of 450MPa and a holding time of 2 seconds; in an ammonia decomposition atmosphere, the powder blank is uniformly heated from room temperature to 500-550℃ at a heating rate of 6-8℃ per minute, and after keeping the temperature for 45 minutes, a pressure of 2.5MPa is applied to the powder blank, and the powder blank is continuously heated to 950℃. After keeping the temperature for 2.5 hours, the powder blank is uniformly cooled to below 100℃ at a cooling rate of 4-6℃ and taken out of the furnace to obtain a powder metallurgy copper-based alloy friction plate material. The material properties are as follows: density 5.9g / cm 3 , shear strength 33.5MPa, compressive strength 310MPa, hardness HBW35, the obtained material is made into the finished product of wind power coupling torque limiter friction plate, and then installed for test, the specific pressure is 25MPa, the torque calibration value is 70000NM, the calibration value cannot be reached during the test, the friction plate has been crushed and failed, see Figure 2 .

[0043] Example 1

[0044] Prepare a high-performance powder metallurgy friction plate for a wind power coupling torque limiter, which contains 66.5wt% copper, 17wt% iron, 11wt% granular carbon, 1.5wt% 0.5mm short-cut carbon fiber, 2wt% tin, 0wt% nickel, and 2wt% aluminum oxide. Additionally, 0.5wt% micro powder paraffin and 0.4wt% aviation kerosene are added according to the total amount. The preparation process includes the following steps: Put the weighed materials into a three-dimensional drum mixer and mix for 2 hours; Press the powder blank in a steel mold with a pressing force of 500MPa and a holding pressure time of 1 second; In an atmosphere of decomposed ammonia, heat the powder blank from room temperature to 500 - 530°C at a heating rate of 6 - 8°C per minute, hold for 60 minutes, apply a pressure of 2.5MPa to the powder blank, continue heating to 990°C, hold for 1.5 hours, and then cool uniformly to below 100°C at a cooling rate of 4 - 6°C and take out of the furnace to obtain a high-performance powder metallurgy copper-based alloy friction plate material. Material properties: density 6.1g / cm 3 , shear strength 35MPa, compressive strength 320MPa, hardness HBW45. After making the obtained material into a finished friction plate for a wind power coupling torque limiter and conducting an installation test, the specific pressure is 35MPa, the fatigue life is 104,000 degrees of slip stroke, and the change rate of the torque calibration value (70,000NM) does not exceed ±9%. Measure the friction coefficient of the material according to the GB / T5768 - 2009 standard. Its average static friction coefficient is 0.56 and the dynamic friction coefficient is 0.54. The product performance is excellent. See Figure 3 .

[0045] Example 2

[0046] Prepare a high-performance powder metallurgy friction plate for a wind power coupling torque limiter, which contains 75.5wt% copper, 16wt% iron, 11wt% granular carbon, 1wt% 0.5mm short-cut carbon fiber, 3wt% tin, 1wt% nickel, and 3wt% aluminum oxide. Additionally, 0.4wt% micro powder paraffin and 0.5wt% aviation kerosene are added according to the total amount. The preparation process includes the following steps: Put the weighed materials into a three-dimensional drum mixer and mix for 2.5 hours; Press the powder blank in a steel mold with a pressing force of 550MPa and a holding pressure time of 1 second; In an atmosphere of decomposed ammonia, heat the powder blank from room temperature to 500 - 540°C at a heating rate of 6 - 8°C per minute, hold for 50 minutes, apply a pressure of 2MPa to the powder blank, continue heating to 950°C, hold for 1.5 hours, and then cool uniformly to below 100°C at a cooling rate of 4 - 6°C and take out of the furnace to obtain a high-performance powder metallurgy copper-based alloy friction plate material. Material properties: density 5.9g / cm 3, the shear strength is 34 MPa, the compressive strength is 318 MPa, and the hardness is HBW43. After making the obtained material into a finished friction plate of a wind power coupling torque limiter and conducting an installation test, the specific pressure is 35 MPa, the fatigue life is 102,000 degrees of slip stroke, and the change rate of the torque calibration value (70,000 NM) does not exceed ±10%. According to the GB / T5768-2009 standard, the friction coefficient of the material is measured, and its average static friction coefficient is 0.54 and the dynamic friction coefficient is 0.54. The product has excellent performance.

[0047] Example 3

[0048] Other conditions are the same as those in Example 1, except that: a powder metallurgy high-performance friction plate for a wind power coupling torque limiter is prepared, in which iron is 12 wt%, granular carbon is 8 wt%, 0.5 mm short carbon fiber is 1 wt%, tin is 1 wt%, nickel is 3 wt%, aluminum oxide is 6 wt%, and the rest is copper; for the obtained powder metallurgy copper-based alloy friction plate material, the material properties: density 5.8 g / cm 3 , the shear strength is 31 MPa, the compressive strength is 316 MPa, and the hardness is HBW42. After making the obtained material into a finished friction plate of a wind power coupling torque limiter and conducting an installation test, the specific pressure is 35 MPa, the fatigue life is 105,000 degrees of slip stroke, and the change rate of the torque calibration value (70,000 NM) does not exceed ±10%. According to the GB / T5768-2009 standard, the friction coefficient of the material is measured, and its average static friction coefficient is 0.55 and the dynamic friction coefficient is 0.53.

[0049] Example 4

[0050] Other conditions are the same as those in Example 1, except that: a powder metallurgy high-performance friction plate for a wind power coupling torque limiter is prepared, in which iron is 18 wt%, granular carbon is 10 wt%, 0.5 mm short carbon fiber is 2 wt%, tin is 3 wt%, nickel is 2 wt%, aluminum oxide is 4 wt%, and the rest is copper; for the obtained powder metallurgy copper-based alloy friction plate material, the material properties: density 6.1 g / cm 3 , the shear strength is 35 MPa, the compressive strength is 320 MPa, and the hardness is HBW46. After making the obtained material into a finished friction plate of a wind power coupling torque limiter and conducting an installation test, the specific pressure is 35 MPa, the fatigue life is 120,000 degrees of slip stroke, and the change rate of the torque calibration value (70,000 NM) does not exceed ±10%. According to the GB / T5768-2009 standard, the friction coefficient of the material is measured, and its average static friction coefficient is 0.54 and the dynamic friction coefficient is 0.53.

[0051] Example 5

[0052] Other conditions are the same as those in Example 1, except that: the average length of the chopped carbon fiber is 1.5 mm; for the obtained powder metallurgy copper-based alloy friction plate material, the material properties are: density 6.0 g / cm 3 , shear strength 36 MPa, compressive strength 325 MPa, hardness HBW43. After making the obtained material into a finished friction plate for a wind power coupling torque limiter and conducting an installation test, the specific pressure is 35 MPa, the fatigue life is a slipping stroke of 130,000 degrees, and the change rate of the torque calibration value (70,000 NM) does not exceed ±10%. According to the GB / T5768-2009 standard, the friction coefficient of the material is measured, and its average static friction coefficient is 0.55 and the dynamic friction coefficient is 0.54.

[0053] Comparative Example 2

[0054] Other conditions are the same as those in Example 1, except that: prepare a powder metallurgy high-performance friction plate for a wind power coupling torque limiter, in which copper is 66.5 wt%, iron is 17 wt%, particulate carbon is 5 wt%, 0.5 mm chopped carbon fiber is 6.5 wt%, flake graphite is 1 wt%, tin is 2 wt%, nickel is 0 wt%, and aluminum oxide is 2 wt%. For the obtained powder metallurgy copper-based alloy friction plate material, the material properties are: density 5.9 g / cm 3 , shear strength 34 MPa, compressive strength 310 MPa, hardness HBW40. After making the obtained material into a finished friction plate for a wind power coupling torque limiter and conducting an installation test, the specific pressure is 35 MPa, the fatigue life is a slipping stroke of 35,000 degrees, and the change rate of the torque calibration value (70,000 NM) does not exceed ±10%. According to the GB / T5768-2009 standard, the friction coefficient of the material is measured, and its average static friction coefficient is 0.42 and the dynamic friction coefficient is 0.40.

[0055] Comparative Example 3

[0056] Other conditions are the same as those in Example 1, except that: prepare a powder metallurgy high-performance friction plate for a wind power coupling torque limiter, in which copper is 66.5 wt%, iron is 17 wt%, particulate carbon is 11.5 wt%, flake graphite is 1.5 wt%, tin is 2 wt%, nickel is 0 wt%, and aluminum oxide is 2 wt%. For the obtained powder metallurgy copper-based alloy friction plate material, the material properties are: density 5.8 g / cm 3 , shear strength 33 MPa, compressive strength 320 MPa, hardness HBW39. After making the obtained material into a finished friction plate for a wind power coupling torque limiter and conducting an installation test, the specific pressure is 35 MPa, the fatigue life is a slipping stroke of 25,000 degrees, and the change rate of the torque calibration value (70,000 NM) does not exceed ±10%. According to the GB / T5768-2009 standard, the friction coefficient of the material is measured, and its average static friction coefficient is 0.4 and the dynamic friction coefficient is 0.39.

Claims

1. A copper-based alloy friction plate for a torque limiter of a wind power coupling, characterized in that: It consists of the following components by mass ratio: Carbon 9 - 14%, tin 1 - 3%, friction component 2 - 8%, iron 12 - 18%, nickel 0 - 3%, and the balance is copper; The copper-based alloy friction plate of the wind power coupling torque limiter is prepared by the following steps: Step 1: Batching Weigh the copper, carbon, tin, friction component, iron, and nickel component materials according to the designed alloy composition ratio. At the same time, add micro-powder paraffin powder additionally by 0.4 - 0.6% of the total mass of the materials; add aviation kerosene additionally by 0.3 - 0.5% of the total mass of the materials; the micro-powder paraffin powder and aviation kerosene are removed during the sintering process; the copper, tin, iron, and nickel are added in the form of master alloy powder, the carbon is added in the form of granular carbon and short carbon fibers, and the friction component is added in the form of compound powder; the mass ratio of granular carbon to short carbon fibers is 9 - 15:0.5 - 2; Step 2: Mixing and forming Mix the weighed various material powders evenly and place them in a steel mold, and press them with a forming pressure of 450 - 550 MPa to obtain a powder compact, Step 3: Sintering In an atmosphere of decomposed ammonia, heat the powder compact to 500 - 550 °C and hold for 0.5 - 1 hour. After the holding is completed, continue to heat to 950 - 990 °C and hold for 2 - 2.5 hours, then cool to below 100 °C and take out of the furnace to obtain a sintered blank of the copper-based alloy friction plate; Step 4: Machining According to the designed dimensional requirements, machine the obtained sintered blank of the copper-based alloy friction plate to obtain the finished friction plate.

2. A copper-based alloy friction plate of a wind power coupling torque limiter according to claim 1, characterized in that: In step 1, the metal powder passes through a 320-mesh sieve, and the undersize is taken; the metal powder provides copper, tin, iron, and nickel in the copper-based alloy friction plate of the wind power coupling torque limiter, the average particle size of the granular carbon is less than or equal to 200 um, the length of the short carbon fiber is 0.4 - 2 mm, and the diameter is 5 - 10 microns; the average particle size of the friction component powder is 150 um.

3. A copper-based alloy friction plate for a wind power coupling torque limiter according to claim 1, characterized in that: The friction component is selected from at least one of aluminum oxide, zirconia, silicon carbide, and silicon oxide.

4. A copper-based alloy friction plate for a torque limiter of a wind power coupling according to claim 1, characterized in that: The mixing is completed in a three-dimensional drum mixer, and the mixing time is 1.5 - 2.5 hours.

5. A copper-based alloy friction plate for a wind power coupling torque limiter according to claim 1, characterized in that: In step two, the density of the powder green body is 5.8 - 5.9 g / cm 3 .

6. A copper-based alloy friction plate for a torque limiter of a wind power coupling according to claim 1, characterized in that: In step 3, the heating rate is 6 - 8 °C / min; the cooling rate is 4 - 6 °C / min.

7. A copper-based alloy friction plate for a torque limiter of a wind power coupling according to claim 1, characterized in that: After the holding at 500 - 550 °C in step 3 is completed, apply a pressure of 2 - 3 MPa to the powder compact and maintain the pressure until the sintering and cooling are completed.

8. A copper-based alloy friction plate for a torque limiter of a wind power coupling according to claim 1, characterized in that: Step 3 The density of the copper-based alloy friction plate sintered green body is 5.9 - 6.1 g / cm 3 .

9. A copper-based alloy friction plate for a wind power coupling torque limiter according to claim 1, characterized in that: The shear strength of the sintered blank of the copper-based alloy friction plate obtained in step 3 is 30 - 35 MPa, the compressive strength is 300 - 320 MPa, and the hardness is HBW40 - 48.

10. A copper-based alloy friction plate for a torque limiter of a wind power coupling according to claim 8, characterized in that: The obtained copper-based alloy friction plate of the wind power coupling torque limiter is applied under a specific pressure of 35 MPa, and the service life is that the slipping stroke exceeds 100,000 degrees, and the change rate of the torque calibration value does not exceed ±10%.

Citation Information

Cited By

  • Copper-based powder metallurgy friction plate for wind power torque limiter and preparation method of copper-based powder metallurgy friction plate

    CN121797962A

  • A copper-based powder metallurgy friction pad for a wind power torque limiter and its preparation method

    CN121797962B